Globalization and Alternative Localities - Ulin, Robert C. (Anthropologica, 2022)
This paper argues against the all too common dichotomy of globalization into a process of homogenization or a process of significant diversification. The paper seeks to bridge this dichotomy by arguing for the relative autonomy of culture with respect to global political-economy, for the plurality of voices that constitute ongoing social interaction, and for a vision of actors operating in fields of power that position human agents differentially. The essay makes use of world systems theory to illustrate the merits and problems of global analysis while focussing on the ethnographic examples of French and Michigan wine growers.